Changes of liver transaminases levels during one year follow up of Deferasirox treatment in children with β-thalassemia major - Hafidh, Nashwan M Al; Younis, Mozahim S (Bangladesh Journal of Medical Science, 2020)
Objectives: Abnormal liver function tests lead to interruptions of Deferasirox therapy. The aim of this study is to determine the changes in liver transaminases levels in pediatric patients with β -thalassemia major during one year follow up of Deferasirox treatment. Material and methods: This study was conducted at Ibn Al Atheer center of thalassemia, Mosul city, Iraq during the period from 3rd of February 2013 till 2nd of February 2014. Seventy one pediatric patients with β -thalassemia major were included in the study. Alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were measured every 4 weeks after starting Deferasirox therapy dose of 30 mg /kg/day for one year. Results: In comparison to mean baseline ALT values, there were significant elevations of mean ALT values in each of the subsequent 4-weekly interval readingsafter Deferasirox therapy. There was nearly eleven times relative risk of having ALT ≥ 5 upper normal level (UNL) in patient with abnormal baseline ALT (Odd ratio 10.96,95% Confidence Interval: lower 2.05, upper 58.58). During a year of study, Deferasirox therapy was associated withALT readings of ≥ 5UNL in 22(31%) of pediatric β-thalassemia patients and that elevation lasted for 4 weeks in 95.5% of patients. Conclusions: Elevated ALT of ≥ 5UNL after Deferasirox therapy was short- lived, and lasted for 4 weeks in 95.5% of patients. It is advisable to start Deferasirox therapy at a dose of 30 mg /kg / day when baseline ALT level is normal. Bangladesh Journal of Medical Science Vol.19(3) 2020 p.453-457